Viabilidade financeira de uma granja produtora de ovos, pintainhos e ração: estudo de caso - Lange, Nestor Elias (2024)
his study aimed to analyze the financial feasibility of egg production, chick rearing, and feed manufacturing at Granja X. The methodology employed involved data collection at Granja X, which was analyzed using financial mathematics methods such as NPV, PI, IRR, and Payback. Data collection took place between March and April 2023. The results indicated the financial viability of Granja X's activities, with egg production, chick rearing, and feed manufacturing showing promise in terms of financial return. For future projects, it is recommended to prioritize the implementation of systems for recording and monitoring financial transactions and costs, thereby simplifying the financial feasibility analysis process.